Menstrual Management and the Negotiation of Failed Femininities: A Discursive Study Among Low-Income Young Women in Aotearoa (New Zealand). Issue 2 (2nd April 2020) - Wootton, Sheralee; Morison, Tracy
Abstract: The dominant discourse of menstrual hygiene management presents successful containment of menstruation as crucial to "successful" Western femininity. Yet, little research in "developed" contexts has examined how compromised "menstrual hygiene management"—as in instances of menstrual poverty—shapes gender identity construction. In this discursive feminist study designed to address this oversight, we analyzed identity work in 12 narratives from economically deprived young women in Aotearoa (New Zealand). The results show how the politics of disgust govern talk and practice regarding menstruation in ways that engender both compliance and attempts at resistance. The results provide insights useful for designing interventions and suggest further research into menstrual poverty in developed contexts.